"This sea which utters me": Reading W. S. Graham's "The Nightfishing" in the Theological Wake of G. M. Hopkins's "The Wreck of the Deutschland" - Brewbaker, Will (Christianity & literature, 2024)
Despite the scant attention paid to his poetic oeuvre in U.S. academic circles, the Scottish poet W. S. Graham stands as one of the most theologically enigmatic poets of the mid-twentieth century. In this essay, I read his major poem, “The Nightfishing” (1955), as a response to G. M. Hopkins’s own seafaring poem, “The Wreck of the Deutschland.” By considering Graham alongside Hopkins, I attempt to draw out the former’s “minimal” theological poetics. More specifically, I consider the way that Graham’s poem both sustains and develops a set of theological questions that stand, too, at the core of Hopkins’s poem.